Synthesis and Characterization of a New Norfloxacin/Resorcinol Cocrystal with Enhanced Solubility and Dissolution Profile - Hanan Fael; Rafael Barbas; Rafel Prohens; Clara Ràfols; Elisabet Fuguet (Pharmaceutics, 2021)
A new cocrystal of Norfloxacin, a poorly soluble fluoroquinolone antibiotic, has been synthetized by a solvent-mediated transformation experiment in toluene, using resorcinol as a coformer. The new cocrystal exists in both anhydrous and monohydrate forms with the same (1:1) Norfloxacin/resorcinol stoichiometry. The solubility of Norfloxacin and the hydrated cocrystal were determined by the shake-flask method. While Norfloxacin has a solubility of 0.32 ± 0.02 mg/mL, the cocrystal has a solubility of 2.64 ± 0.39 mg/mL, approximately 10-fold higher. The dissolution rate was tested at four biorelevant pH levels of the gastrointestinal tract: 2.0, 4.0, 5.5, and 7.4. In a first set of comparative tests, the dissolution rate of Norfloxacin and the cocrystal was determined separately at each pH value. Both solid forms showed the highest dissolution rate at pH 2.0, where Norfloxacin is totally protonated. Then, the dissolution rate decreases as pH increases. In a second set of experiments, the dissolution of the cocrystal was evaluated by a unique dissolution test, in which the pH dynamically changed from 2.0 to 7.4, stepping 30 min at each of the four biorelevant pH values. Results were quite different in this case, since dissolution at pH 2 affects the behavior of Norfloxacin at the rest of the pH values.